Answer:
![f(x)+g(x)=5x^{3} +4x^{2}+x-8](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D5x%5E%7B3%7D%20%2B4x%5E%7B2%7D%2Bx-8)
Step-by-step explanation:
Given:
Two functions are given:
![f(x)=5x^{3} +3x^{2} -3](https://tex.z-dn.net/?f=f%28x%29%3D5x%5E%7B3%7D%20%2B3x%5E%7B2%7D%20-3)
![g(x)=x^{2} +x-5](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E%7B2%7D%20%2Bx-5)
Find ![f(x)+g(x)](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29)
Solution:
![f(x)+g(x)=(5x^{3} +3x^{2} -3)+(x^{2} +x-5)](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D%285x%5E%7B3%7D%20%2B3x%5E%7B2%7D%20-3%29%2B%28x%5E%7B2%7D%20%2Bx-5%29)
![f(x)+g(x)=5x^{3} +3x^{2} -3+x^{2} +x-5](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D5x%5E%7B3%7D%20%2B3x%5E%7B2%7D%20-3%2Bx%5E%7B2%7D%20%2Bx-5)
![f(x)+g(x)=5x^{3} +(3x^{2} +x^{2})+x-3-5](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D5x%5E%7B3%7D%20%2B%283x%5E%7B2%7D%20%2Bx%5E%7B2%7D%29%2Bx-3-5)
![f(x)+g(x)=5x^{3} +4x^{2}+x-8](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D5x%5E%7B3%7D%20%2B4x%5E%7B2%7D%2Bx-8)
Therefore, the function of ![f(x)+g(x)=5x^{3} +4x^{2}+x-8](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D5x%5E%7B3%7D%20%2B4x%5E%7B2%7D%2Bx-8)
Try out this website or search "surface area of a triangular prism" in Google
http://www.ck12.org/geometry/Surface-Area-of-Triangular-Prisms/lesson/Surface-Area-of-Triangular-Pri...
Slope is given by the expression:
![m=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
We can equal both slopes of mAC and mCE
![\begin{gathered} \frac{3-6}{-1-(-3)}=\frac{-3-3}{3-(-1)} \\ \\ \frac{-3}{2}=-\frac{6}{4} \\ -\frac{3}{2}=-\frac{3}{2} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B3-6%7D%7B-1-%28-3%29%7D%3D%5Cfrac%7B-3-3%7D%7B3-%28-1%29%7D%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B-3%7D%7B2%7D%3D-%5Cfrac%7B6%7D%7B4%7D%20%5C%5C%20-%5Cfrac%7B3%7D%7B2%7D%3D-%5Cfrac%7B3%7D%7B2%7D%20%5Cend%7Bgathered%7D)
Answer is B.
Answer: 26
Step-by-step explanation:
The product of (x1)^2 is 20